Ambient noise tomography across the southern Alaskan Cordillera. Issue 9 (5th May 2015) - Ward, Kevin M.
Abstract I present the results of an extensive data mining effort integrating 197 permanent and temporary seismic stations into a Rayleigh wave ambient noise study across southern Alaska and westernmost Canada. Principal observations of my tomography model are largely consistent with mapped geology features and previous geophysical studies while providing previously unavailable, laterally continuous details of the southern Alaskan Cordillera lithosphere. At intermediate periods, a geophysically uniform crust is observed north of the Denali Fault and is consistent with a sharp transition in crustal thickness. Under the Wrangell volcanic belt, a prominent low‐phase‐velocity anomaly correlates well with the lateral extent of a relative low‐gravity anomaly and Neogene surface volcanics. At longer periods, a low‐phase‐velocity anomaly bounds the inferred eastern extent of the subducted Yakutat microplate beneath the Wrangell volcanic belt.